Functional Recovery in Osteoarthritic Chondrocytes Through Hyaluronic Acid and Platelet-Rich Plasma–Inhibited Infrapatellar Fat Pad Adipocytes. (October 2016) - Chen, Wei-Hong; Lin, Chien-Min; Huang, Chiung-Fang; Hsu, Wei-Che; Lee, Chian-Her; Ou, Keng-Liang; Dubey, Navneet Kumar; Deng, Win-Ping
Background: Recent studies have shown evidence that higher adiposity in the infrapatellar fat pad (IFP) induces inflammatory phenotypes in the knee joint and thereby contributes to the development and progression of osteoarthritis (OA). In particular, IFP adipocyte–derived inflammatory cytokines participate in pathological events. Our previous research has already addressed the therapeutic efficacy of hyaluronic acid and platelet-rich plasma (HA+PRP), including the promotion of cartilage regeneration and the inhibition of inflammation. The current study aimed to explore the remedial action of coadministered HA+PRP in OA recovery via IFP adipocyte inhibition. Hypothesis: HA+PRP repairs OA articular cartilage by inhibiting the release of adipokines from IFP adipocytes. Study Design: Controlled laboratory study. Methods: IFP adipocytes and articular chondrocytes were obtained from 10 patients with OA, and the effects of releasates containing cytokines and adipokines in IFP adipocyte–derived conditioned medium (IACM) on articular chondrocytes and IFP adipocytes themselves were evaluated. The therapeutic efficacy of exogenous HA+PRP was determined through its administration to cocultured IFP adipocytes and articular chondrocytes and further demonstrated in a 3-dimensional (3D) arthritic neocartilage model. Results: The IACM and IFP adipocyte–induced microenvironment could induce dedifferentiated and inflammatory phenotypes in articular chondrocytes. HA+PRP decreased the inflammatory potential of IFP adipocytes through the profound inhibition of cytokines and adipokines. The IACM-mediated and -reduced cartilaginous extracellular matrix could also be recovered through HA+PRP in the 3D arthritic neocartilage model. Conclusion: IFP adipocyte–derived releasates mediated inflammatory response dedifferentiation in chondrocytes, which was recovered through HA+PRP administration. Clinical Relevance: Our findings demonstrated that HA+PRP effectively diminished IFP adipocyte–promoted inflammation in articular chondrocytes, indicating that the IFP could be a potential therapeutic target for OA therapy.